KARAKTERISTISASI DAN UJI HOMOGENITAS KANDIDAT BAHAN ACUAN BUFER FTALAT DAN BUFER FOSFAT UNTUK PENGUKURAN DERAJAT KEASAMAN - Sujarwo Sujarwo; Nuryatini Nuryatini (Jurnal Kimia Terapan Indonesia, 2013)
Measurement of pH is closely related to everyday life,such as in the area of environment, food and beverage,pharmaceuticals, and even metabolism process in humanbody. To ensure the quality of pH measurement, pH metershould be calibrated regularly and checked each time beforeused. Calibration and performance checking of pH meterrequires traceable standard. The standard should be linked toCRM (Certified Reference Materials). Research Center forChemistry - Indonesian Institute of Sciencesas the technicallaboratory in Indonesia for metrology in chemistry isconducting research in developing reference materials for pHmeasurement. The reference materials are phthalate andphosphate buffer withthe value of pH were 4.00Â±O.OJ and6.86Â±O. OJ, respectively at 95% confidence level (k=2).Homogenity study was evaluated based on F-test and theresults indicated that both reference materials candidate werehomogeneous.Keywords: Reference materials, CRM,phthalate buffer,phosphatebuffer,uncertainty,homogeneity.